Penerapan Model Student Teams Achiement Divisions untuk Meningkatkan Hasil Belajar Matematika Kelas IV SD 8 Kandangmas - Susanti Susanti (Elementary: Islamic Teacher Journal, 2019)
This study aims to improve student learning outcomes using the Student Teams Achiement Divisions learning model for fourth grade students of SD 8 Kandangmas. This study uses Classroom Action Research, consisting of four stages, namely: planning, implementation, observation, and reflection. The results of this study show that the results of observation of learning activities in the first cycle reached 69% with the criteria of Enough and the second cycle increased to 83% with the criteria of Good. The observation results of the management of teacher learning in the first cycle reached 78% with the criteria of Good and in the second cycle increased to 88% with the criteria Very Good. The results of student evaluation tests in the pre-cycle with an average value of 57, in the first cycle increased to 74 and in the second cycle to 86 with the criteria complete. the average learning outcomes achieved 85.3 with classical completeness reaching 90%. The conclusion of this study is through the use of the Student Teams Achiement Divisions learning model can improve the learning outcomes of fourth grade students of SD 8 Kandangmas.